EARLY CONGENITAL SYPHILIS: CLINICAL AND LABORATORY FEATURES IN THE NEONATAL PERIOD - N. V. Matyskina; T. E. Taranushenko; V. I. Prokhorenkov (Детские инфекции (Москва), 2015)
Syphilis remains one of the very disturbing inflections. The highest morbidity rate is registered among women at the age of 18—29 years old. The percentage of pregnant women in the General statistics of syphilis incidence is 8 to 12%. Against this background, the syphilis incidence among newborn infants is an extremely serious problem. The article presents the clinical case of early congenital syphilis in the newborn baby.